Chemodiversity, biosynthetic regulation, and functional roles of Eucalyptus phenolics: applications and prospects - Pérez-Martínez, Jordán; Maldonado, Carlos; Mora-Poblete, Freddy (Frontiers in Plant Science, 2026)
Eucalyptus species constitute a rich reservoir of bioactive phenolic compounds. In contrast to the extensively characterized essential oils, the non-volatile phenolic fraction remains fragmented across the literature and insufficiently integrated from biochemical, ecological, and applied perspectives. This review synthesizes current evidence on the structural diversity, tissue distribution, and biosynthetic regulation of Eucalyptus phenolics, and uniquely bridges their ecological functions with their translational relevance in pharmaceutical, agricultural (biopesticides), and environmental applications. Quantitative analyses indicate that lignified organs such as bark and stump wood consistently contain the highest phenolic concentrations, reaching 474.9 mg/g in E. camaldulensis bark, whereas foliar tissues show pronounced intra- and interspecific variation driven by extraction polarity. We identify a critical gap in the field: although over 103 phenolic compounds have been documented, many reports lack methodological standardization, quantitative reproducibility, and chemometric alignment, limiting their comparability and downstream industrial translation. Across organs, several dominant phenolics are recurrently identified, including ellagic acid, epicatechin, gallic acid, quercetin-glucuronide, and sinapic acid. Bark of E. urograndis, E. grandis, and E. camaldulensis is especially enriched in ellagitannins and flavan-3-ols, while leaf extracts of E. globulus accumulate high levels of glucuronidated flavonols. Distinctive metabolites, including rosmarinic acid, occur only in E. marginata. Beyond compositional surveys, this review examines biosynthetic regulation, ecological roles, and emerging technological applications. We highlight that persistent challenges include extraction standardization, metabolic engineering, and the design of biodelivery systems. Overall, this review positions Eucalyptus phenolics as strong candidates for innovation, while providing a clearer roadmap to overcome persistent limitations, particularly in compound-specific bioactivities, transcriptional and metabolic regulatory pathways, and genotype–environment–management interactions.